THE EFFECT OF SCHOOL BASED MANAGEMENT TO TEACHER PROFESSIONALISM OF SENIOR HIGH SCHOOL IN CENTRAL LAMPUNG - Sumali, Sumali (Universitas Muhammadiyah Metro, 2016)
This study aims to find out there is a direct effect of school-based management in the professionalism of teachers. Subjects were teachers who served in secondary schools in Central Lampung, participants were 40 teachers. The study used a survey method causal. The study proved that the school-based management influence on the professionalism of teachers. This means that peninggkatan professionalism of teachers is essentially the improvement of the quality of education within the scope of narrow and wide, can be done by increasing the school-based management.